Pengaruh Struktur Kepemilikan, Struktur Modal Dan Persistensi Laba Terhadap Kualitas Laba - Jionike Priskanodi; Sri Trisnaningsih; Invony Dwi Aprilisanda (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
Earning information was the most etential information in financial statement. Earning reflected company performance, company success, also predicted future cash flow. Earnings quality was as important as earning information itself. Lack off earning information could lead to bad decision making. Because of that, this research aims to test the effect of ownership structure, capital structure, and earning persistence on earning quality.            This research used secondary data in the form of financial statement and annual report of the company. This resarch used population from the consumer goods company that listed in Indonesia Stock Excahange (IDX) on 2016-2019, with 26 company sample that choosen by purposive sampling method. Normality test, classic assumption test, hipotesist test, and multiple linear regression are used to fulfill the aim of this research.            The results of this show that (1) ownership structure has no significant effect on earning quality, (2) capital structure has no significant effect on earning quality, (3) earning persistence has no significant effect on earning quality, (4) ownership structure, capital structure, and earnig persistence have no significant effect on earning quality simultaneously.